Fremanezumab in real-life clinical practice: specialized headache center experience - Yu. E. Azimova; K. V. Skorobogatikh; V. V. Osipova; D. Z. Korobkova; N. V. Vashchenko; E. Z. Mamkhegov; A. S. Galanina; E. A. Guziy (Неврология, нейропсихиатрия, психосоматика)
Anti-CGRP monoclonal antibodies (mAb) have been approved and successfully used in Russia since 2020.Objective: to investigate the efficacy and safety of fremanezumab (FRE) therapy (225 mg monthly or 675 mg quarterly) in real-life clinical practice in patients with migraine who referred to a specialized Russian headache center.Material and methods. This open-label, retrospective study involved 202 patients (mean age 39.4±12.2 years) with frequent episodic (EM) or chronic migraine (CM) who received at least three injections of FRE 225 mg or three injections with a total dose of 675 mg and regularly completed the Migrebot headache diary one month before starting therapy and throughout the course of treatment.Results. The mean number of migraine days per month decreased in the whole group from 20.1±8.2 (before treatment) to 8.5±7.9 after 12 weeks (p<0.0001), in the EM group from 10.9±4.1 to 3.6±3.7 (p<0.0001) and in the CM group - from 24.4±5.7 to 10.8±8.3 (p<0.0001). Adverse events were observed in 13 (6.4%) patients (most frequently local reactions: itching, rash, redness, induration at the injection site).Conclusion. The study showed a favourable efficacy and safety profile of FRE in the Russian population, where anti-CGRP mAbs are considered the first-line treatment for migraine.